DOSAGEM DE CONCRETOS PARA USO EM PLACAS DE PISOS ELEVADOS EXTERNOS - Paiva, José Antônio; Costa, Larissa; Velasco, Reila; Varela, Wendell (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The raised floor technology for outdoor areas has a great potential to increase the performance (by the materials used) and the economic efficiency of the buildings (by the construction process), by allowing less costly interventions, such as access to facilities arranged in the free space between the raised floor and the slab. With NBR 15805 (ABNT,2010) enhanced the efficiency of construction leaving aside the empiricism previously practiced. However, there are still deficiencies in the execution and performance of the plate, especially with respect to its durability. The present paper aims to study the performance of precast concrete specifically designed for use in external raised floors with different configurations of materials and constituent elements in order to achieve improvements in durability and strength. It is studied the incorporation of steel fiber and recycled aggregates of concrete residues, the latter focusing on environmental issues. This study serves as a basis for a broader study of the performance of plates with these materials and with different thicknesses, shapes and armor positions traditionally used in this type of plate.